Human Rights and Memory - Levy, Daniel, 1962- (Book collections on Project MUSE., 2010)
"Examines the foundations of human rights, how their political and cultural validation in a global context is posing challenges to nation-state sovereignty, and how they become an integral part of international relations and are institutionalized into domestic legal and political practices"--Provided by publisher